Web-based network device management using SNMP servlet - Hossen, Md. Jakir; Ramli, Abdul Rahman; Abdullah, Mohamad Khazani (IEEE, 2003)
As the complexity and size of data networks increases, network management faces a great challenge. Fortunately, the emergence of the SNMP (simple network management protocol) management framework and Web technology release network managers from the difficult circumstance. The paper explains the function and design of a prototype network device management station based on leading-edge Java servlet technologies and the World Wide Web. Web technologies bring valuable cost improvements, flexibility, and security enhancement to configuration management and performance management. The paper also discusses the functional requirements of Web-based network management and proposes the architecture for Web-based network configuration management, which is capable of controlling and monitoring remotely the configuration information of enterprise networks.